A cluster of Epoetin-associated pure red cell aplasia: clinical features and the possible association of HLA-DRB1*12:02. (July 2016) - Tan, Chuen Wen; Tan-Koi, Wei-Chuen; Ng, Jennifer; Chan, Choong Meng; Hwang, William Ying Khee
Antibody-mediated pure red cell aplasia is a rare but serious complication in chronic kidney disease patients receiving recombinant human erythropoietin (r-HuEpo). Between April 2012 and May 2013, eight such cases were reported in our institution. Their clinical features were reviewed and their HLA alleles were compared with those of healthy controls. All patients were exposed to epoetin alfa (Eprex ® ) with polysorbate-80 as stabilizer via subcutaneous route with a mean age of 61.9 years and mean exposure of 11.2 months of r-HuEpo before loss of efficacy. 87.5% of the cases were male and Chinese and received immunosuppression as treatment for pure red cell aplasia. All three of the successfully treated patients are alive compared with only 40% of the transfusion-dependent patients. DRB1*12:02 was more frequently expressed among the cases than healthy controls suggesting a plausible molecular link.